2015
DOI: 10.1142/s0219061315500099
|View full text |Cite
|
Sign up to set email alerts
|

On model-theoretic connected components in some group extensions

Abstract: We analyze model-theoretic connected components in extensions of a given group by abelian groups which are defined by means of 2-cocycles with finite image. We characterize, in terms of these 2-cocycles, when the smallest type-definable subgroup of the corresponding extension differs from the smallest invariant subgroup. In some situations, we also describe the quotient of these two connected components.Using our general results about extensions of groups together with Matsumoto-Moore theory or various quasi-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(47 citation statements)
references
References 23 publications
0
47
0
Order By: Relevance
“…In [3], the authors have shown that such extensions can, under some additional assumptions, give new examples of definable groups with G 00 = G 000 , building upon and extending the intuitions from the first known example with this property, found in [5], namely the universal cover of SL 2 (R). They also pose some questions and conjectures, one of which will be proved at the end of this section.…”
Section: ( † †)mentioning
confidence: 93%
See 4 more Smart Citations
“…In [3], the authors have shown that such extensions can, under some additional assumptions, give new examples of definable groups with G 00 = G 000 , building upon and extending the intuitions from the first known example with this property, found in [5], namely the universal cover of SL 2 (R). They also pose some questions and conjectures, one of which will be proved at the end of this section.…”
Section: ( † †)mentioning
confidence: 93%
“…The above conjectures are important mostly for two reasons: (1) They imply that Corollary 2.8 in [3] holds in general (i.e., also when the language is uncountable), that is: in Theorem 5.5, if G 00 B = G 000 B and A * 1 ⊆ G 000 B ∩ A, then the assumption (i) (about the nonsplitting of the modified 2-cocycle) not only implies (under the assumption (ii)), but is also necessary for G 00 B = G 000 B . This is explained in detail in [3]. (2) They imply that, in a rather general context, the quotient G 00 / G 000 is (algebraically) isomorphic to the quotient of a compact group by a finitely generated dense subgroup (this will be revisited at the end of this section).…”
Section: Application Of the Main Theorem In Group Extensionsmentioning
confidence: 99%
See 3 more Smart Citations